Randomized phase 2 study comparing irinotecan versus amrubicin as maintenance therapy after first‐line induction therapy for extensive disease small cell lung cancer (HOT1401/NJLCG1401). Issue 14 (2nd June 2021) - Tanaka, Hisashi; Hasegawa, Yukihiro; Fujita, Yuka; Nakamura, Atsushi; Kikuchi, Eiki; Kawai, Yasutaka; Harada, Toshiyuki; Watanabe, Naomi; Yokouchi, Hiroshi; Usui, Kazuhiro; Saito, Ryota; Watanabe, Hiroshi; et al.
Abstract: Background: A cisplatin plus irinotecan (CPT‐11) regimen is used for patients with extensive disease small cell lung cancer (ED‐SCLC). Amrubicin (AMR) is primarily used for relapsed SCLC. The HOT1401/NJLCG1401 trial, an open‐label randomized phase II trial, was designed to assess the benefit of maintenance therapy in patients with ED‐SCLC who responded to induction therapy. Methods: Patients with histologically‐ or cytologically‐confirmed ED‐SCLC were included and were treated with an induction therapy of four cycles of cisplatin (60 mg/m 2 on day 1) plus CPT‐11 (60 mg/m 2 on days 1, 8, and 15) every four weeks. After induction therapy, patients who had nonprogressive disease were randomized to receive either maintenance CPT‐11 (60 mg/m 2 on days 1 and 8) every three weeks, or AMR (35 mg/m 2 on days 1–3) every three weeks. Results: A total of 34 patients were enrolled; 20 patients had progressive disease or received incomplete induction chemotherapy. Finally, 14 patients were randomly assigned to receive CPT‐11 ( n = 7) or AMR ( n = 7). This study was terminated prematurely because of low patient accrual. The overall objective response rate was 73%, the median PFS was 5.7 months (95% confidence interval [CI]: 3.6–11.8), and the median overall survival was 20.1 months (95% CI: 13.7–not reached). No statistically significant difference in progression‐free survival (PFS) were noted between patients treated with CPT‐11 and those treated with AMR. There were no treatment‐related deaths in this study. Conclusions: Maintenance therapy with CPT‐11 or AMR after induction therapy might be effective in some patients. Abstract : There were some patients who achieved long disease control. Maintenance therapy with CPT‐11 or AMR after induction therapy could have potential for treating ED‐SCLC.